2017
DOI: 10.1177/1350508417690396
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the subject behind diversity: Exploring the micro-politics of representation in ethnic minority creatives’ identity work

Abstract: Much literature on the cultural industries celebrates ethnicity as a source of creativity. Despite its positive connotation, this discourse reduces ethnic minority creatives to manifestations of a collective ethnic identity automatically leading to creativity, creating a paradox of creativity without a creative subject. Approaching creatives with an ethnic minority background as agents, this article investigates how they self-reflectively and purposely discursively construct ethnicity as a source of creativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 88 publications
0
31
1
1
Order By: Relevance
“…The refugees demonstrate willingness to adopt the available identity templates rather than resist them in the sense of Collinson (2003). Moreover, and different from prior research indicating that ethnic minority professionals often draw on their ethnic background as a resource in their identity work (Essers and Benschop, 2009; Van Laer and Janssens, 2017; Zanoni et al, 2017), the refugees in our study overwhelmingly view their background as handicap.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The refugees demonstrate willingness to adopt the available identity templates rather than resist them in the sense of Collinson (2003). Moreover, and different from prior research indicating that ethnic minority professionals often draw on their ethnic background as a resource in their identity work (Essers and Benschop, 2009; Van Laer and Janssens, 2017; Zanoni et al, 2017), the refugees in our study overwhelmingly view their background as handicap.…”
Section: Discussioncontrasting
confidence: 88%
“…Partly drawing on Alvesson and Willmott’s identity regulation framework, a large and still growing strand within the critical diversity literature analyses identity construction along the lines of social minority categories such as gender (Kelan, 2010; Ortlieb and Sieben, 2019), ethnicity (Van Laer and Janssens, 2017; Zanoni et al, 2017), religion (Essers and Benschop, 2009), sexuality (Rumens and Broomfield, 2014; Van Laer, 2018) and dis-/ability (Jammaers and Zanoni, 2020). Furthermore, several studies found that organizational practices aimed at fostering diversity and inclusion such as training and promotion procedures trigger identity work of minority group members (Jammaers and Zanoni, 2020; Villesèche et al, 2018; Yang and Bacouel-Jentjens, 2019; Zanoni and Janssens, 2007).…”
Section: Theorising Inclusion and Identitymentioning
confidence: 99%
“…In addition, some studies take a narrative approach to the identity of entrepreneurs, for instance, narratives of ethnicity (Zanoni et al . 2017) or environmental values (Phillips 2013). Such studies can be categorized as looking at the personal identity of entrepreneurs in terms of the ‘narrative self‐understanding’ of their beliefs and feelings (Hitlin 2012).…”
Section: Theoretical Perspectives In Ioe Researchmentioning
confidence: 99%
“…Albinsson 2018; Zanoni et al . 2017). While such empirical complexities will remain, it is essential to clearly differentiate the proposed terminology and operationalizations in future studies to allow for a more coherent understanding of what constitutes the identity of entrepreneurs, how it is formed, maintained, and changed over time, as well as which influences it may assert over individuals, teams, new ventures, or the broader environment.…”
Section: Providing Conceptual Claritymentioning
confidence: 99%
“…How should we understand the role of those who are subject to ‘being included’? Quite often individuals are ‘coercively’ included based on a certain identity characteristic, for instance, being a token representative of a minority group (Ponzoni et al, 2017; Zanoni et al, 2017). Does that lead to new forms of exclusion under the mantle of inclusion?…”
Section: Introductionmentioning
confidence: 99%